Pengaruh Keamanan Sistem Terhadap Kepuasan Aplikasi Dana Di Lingkungan Universitas Muhammadiyah Mamuju - Wahyudi, Ismuaji; Ramadani, Suci Oktavia; Yeni, Hari (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study aims to analyze and prove the influence of system security on user satisfaction of the DANA digital wallet application, specifically within the academic community at Universitas Muhammadiyah Mamuju. The background of this research is based on the phenomenon of shifting from cash to digital transactions, which demands strict guarantees of personal data protection and financial security within the campus environment. The research method used is quantitative with a causal approach. Data were collected by distributing questionnaires to 40 respondents consisting of students and academics at Universitas Muhammadiyah Mamuju who are active DANA users, employing a purposive sampling technique. Data analysis was conducted using simple linear regression, preceded by validity, reliability, and classical assumption tests. The results show that system security has a positive and significant effect on user satisfaction. These findings indicate that the security dimensions, which include data encryption, two-factor authentication (OTP/Biometrics), and privacy policy transparency, are the main determining factors in creating user comfort. Satisfaction in the fintech sector is proven to rely not only on ease of features but more fundamentally on user trust in the platform's security system. The implications of this research suggest the importance of increasing. digital literacy and strengthening cyber security infrastructure to maintain user loyalty in the future.